Analisis BOD dan COD di perairan estuaria Krueng Cut, Banda Aceh - Muhammad Irham; Fauzul Abrar; Viqqi Kurnianda (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2017)
Analysis of BOD and COD has been done at estuary of Cut River in Alue Naga Village from March to April 2017. The purpose of this research was to analysis the water quality in Krueng Cut estuarial area, which is compared to the Government Regulation No. 82/2001. The method used in this research is field survey by employing purposive sampling method and laboratory analysis to the samples obtained in the field.The BOD, COD, DO, nitrate, nitrate was tested at Laboratory of Chemistry, Faculty of Marine and Fishery of Syiah Kuala University by applyingspectrophotometric method using Filterfotometer PF-11. The results showed that the highest concentration of BOD and COD was at station 3 where the mixing region occurred because the freshwater from river uphill meets with salt-water from the ocean, and the lowest BOD and COD concentration was at station 7 whichis the mouth of the estuary. The results obtained that water quality in Krueng Cut waters based on Government Regulation of water quality no. 82/2001 on the water quality categorized as a class III water quality, which is the water that can be used only for the function of fishery cultivation.Analisa BOD dan COD telah dilakukan di perairan Krueng Cut Desa Alue Naga yang dilakukan pada bulan Maret sampai dengan April 2017. Tujuan dari penelitian ini adalah untuk mengetahui kualitas air di perairan Krueng Cut Desa Alue Nagayang dibandingkan dengan Peraturan Pemerintah (PP) nomor 82 Tahun 2001.Metoda yang dilakukan dalam penelitian ini adalah survey lapangan dengan metode purposive sampling dan analisa laboratorium terhadap sampel yang diperoleh di lapangan untuk uji BOD, COD, DO, nitrat, nitrit di Laboratorium Kimia Laut Fakultas Kelautan dan Perikanan Universitas Syiah Kualadengan metoda Spektofotometri Filterfotometer PF-11. Hasil penelitian menunjukkan bahwa konsentrasi BOD dan COD tertinggi berada pada stasiun 3 yaitu daerah sirkulasi arus (pertemuan antara arus air tawar dan air asin), dan konsentrasi BOD dan COD terendah berada di stasiun 7 yang merupakan daerah mulut estuari. Hasil penelitian diperoleh bahwa kualitas air di perairan Krueng Cut berdasarkanPeraturan Pemerintah No. 82 Tahun 2001 tentang kualitas air baku mutu dikatagorikan sebagai kualitas air kelas III yaitu air yang dapat digunakan hanya untuk fungsi pembudidayaan perikanan.